The 825 Ma Yiyang high–MgO basalts of central South China: Insights from Os–Hf–Nd data - Wu, T.; Wang, Xuan-Ce; Li, W.; Wilde, Simon; Tian, L.; Pang, C.; Li, J. (Elsevier Science BV, 2018)
© 2018 Elsevier B.V. High–MgO basaltic lavas, including komatiites and picrites, have long been used as probes of both the chemical and thermal evolution of the mantle through time. The ca. 825 Ma Yiyang high–MgO basalts in the central South China Block (SCB) were considered to be the first evidence for >1500 °C mantle melts by a Rodinian mantle plume. However, later studies proposed that they may have been generated within an arc setting and can be classified as boninites. Here we present a comprehensive Os–Hf–Nd isotopic study of the Yiyang basalts. The Yiyang basalts have high MgO (>10%), Ni (>182 ppm), Cr (>667 ppm) and Os contents (mostly >0.3 ppb) with radiogenic Os isotopes ((187Os/188Os)i = 0.134 to 0.282). They have relatively uniform whole–rock Nd and Hf isotopes with eNd(t) and eHf(t) values ranging from -3.7 to -1.3 and from +2.9 to +4.3, respectively. Our new data indicate that although crustal assimilation and fractional crystallization (AFC) may have played a role in the geochemical diversity of the Yiyang basalts, the enrichment in light rare earth elements (LREE) and large–ion lithophile elements (LILE) relative to high field strength elements (HSFE) most likely are features of the primary magma. The Yiyang high–MgO basalts, along with contemporary high–MgO basalts in the central SCB, have lower SiO2 contents, and Al2O3/TiO2 ratios, but higher TiO2, Zr, Nb, and Nd contents and Th/U ratios than typical boninites. The presence of negative Ba anomalies and depletion in middle REE (MREE) to heavy REE (HREE) in these high-MgO basaltic rocks are also distinct from what is observed in typical boninites. Therefore, the primary magma of the Yiyang basalts had similar whole–rock geochemical compositions to that of komatiites and plume–derived basalts. Their decoupled Hf–Nd isotopes indicate that recycled oceanic sediments may have been incorporated into their source. They have primitive mantle–like Al2O3/TiO2 ratios (21-23) and flat HREE patterns. However, unlike other Al–undepleted or Munro–type komatiites, their mantle source did not undergo earlier melting events. Our new results support the view that the Yiyang basalts are komatiitic and not boninitic, and that they were likely derived from a Rodinian mantle plume.